PEMBERDAYAAN KELAS GIZI REMAJA CEGAH STUNTING MELALUI PROGRAM DASHAT DAN EMO DEMO DI SMA SWASTA DARUL HIKMAH DESA PAGUTAN KOTA MATARAM - Septiani, Baiq Dewi Sukma; Ardiansyah, Lalu Dwi Satria; Sulistiawati, Febrina (Universitas Mataram, 2024)
Stunting is a condition of stunted growth and physical development of children, caused by chronic lack of nutritional intake or repeated infections. The impact of stunting not only affects height, but also brain development, intelligence, and productivity of children in the future. Data from the Basic Health Research of West Nusa Tenggara Province shows that the prevalence of adolescent girls aged 16-18 years with very short nutritional status is 2.67% and short nutritional status is 21.79%, while in adolescent boys the very short nutritional status is 4.97% and the short nutritional status category is 70.65% while in Mataram City the prevalence of adolescents aged 16-18 years with very short nutritional status is 0.98% and short nutritional status is 19.99%. The purpose of this activity is to form an adolescent nutrition class to prevent stunting through the Healthy Kitchen to Overcome Stunting (DASHAT) program and Emotional Demonstration through the Snake and Ladder game in an effort to prevent stunting early on. The activity method starts from the Formation of the